Assessment in open and social forms of learning - Class, Barbara; Panes, Mathilde; Carbonel, Henrietta; Jullien, Jean-Michel (Proceedings of the International Conference on Networked Learning, 2026)
The aim of this workshop is to have participants design the assessment of one learning activity using the models provided. Upfront, two methods have been used to produce the models. On one hand, speculative methods to imagine the future of assessment in higeher education institutions and on the other hand a narrative literature review. Models are conceptual representations that make a situation, phenomenon, or process intelligible, serving both scientific and practice purposes. Two of them, including the material provided with them (e.g. rubric, guide, checklist) are attached in French but will be translated in English for the workshop in case of acceptance. The overall theoretical framework connects assessment, social learning and openness.